'Estar' = 'Ser' + X - Gallego, Ángel J.; Uriagereka, Juan (Borealis – An International Journal of Hispanic Linguistics, 2016)
This paper studies the SER / ESTAR alternation in Spanish. Following the logic behind Freeze's (1992) and Kayne's (1993) analysis of Benveniste's (1960) approach to HAVE, it is argued that ESTAR derives from SER plus the incorporation of an additional functional element, labeled X. It is this element (which we argue has a prepositional nature in different languages), and not some lexical property (a feature), that is responsible for the oft-noted aspectual (i.e. non-standing, perfective, stagelevel) flavor of ESTAR. Even though we focus on the SER / ESTAR cut, our analysis ultimately argues for the idea that the distinction between Individual Level and Stage Level predicates does not indicate a 'lexical' (meaning 'primitive,' 'intrinsic,' or 'inherent') property of predicates. In line with recent neoconstructionist approaches to the lexicon (cf. Borer 2005, Hale & Keyser 1993, 2002, Marantz 1997, Ramchand 2008, among others), we pursue the idea that properties (transitivity, lexical aspect, stativity, etc.) that were interpreted as lexical in projectionist and lexicalist models are actually the consequence of a specific syntax.